Secular mantle oxidation across the Archean-Proterozoic boundary: Evidence from V partitioning in komatiites and picrites. (1st April 2019) - Nicklas, Robert W.; Puchtel, Igor S.; Ash, Richard D.; Piccoli, Philip M.; Hanski, Eero; Nisbet, Euan G.; Waterton, Pedro; Pearson, D. Graham; Anbar, Ariel D.
Abstract: The oxygen fugacities of nine mantle-derived komatiitic and picritic systems ranging in age from 3.55 Ga to modern day were determined using the redox-sensitive partitioning of V between liquidus olivine and komatiitic/picritic melt. The combined set of the oxygen fugacity data for seven systems from this study and the six komatiite systems studied by Nicklas et al. (2018), all of which likely represent large regions of the mantle, defines a well-constrained trend indicating an increase in oxygen fugacity of the lavas of ∼1.3 ΔFMQ log units from 3.48 to 1.87 Ga, and a nearly constant oxygen fugacity from 1.87 Ga to the present. The oxygen fugacity data for the 3.55 Ga Schapenburg komatiite system, the mantle source region of which was previously argued to have been isolated from mantle convection within the first 30 Ma of the Solar System history, plot well above the trend and were not included in the regression. These komatiite's anomalously high oxygen fugacity data likely reflect preservation of early-formed magma ocean redox heterogeneities until at least the Paleoarchean. The observed increase in the oxygen fugacity of the studied komatiite and picrite systems of ∼1.3 ΔFMQ log units is shown to be a feature of their mantle source regions and is interpreted to indicate secular oxidation of the mantle between 3.48 and 1.87 Ga. Three mechanisms are considered to account for the observed change in the redox state of the mantle:(1) recycling of altered oceanic crust, (2) venting of oxygen from the core due to inner core crystallization, and (3) convection-driven homogenization of an initially redox-heterogeneous primordial mantle. It is demonstrated that none of the three mechanisms alone can fully explain the observed trend, although mechanism (3) is best supported by the available geochemical data. These new data provide further evidence for mantle involvement in the dramatic increase in the oxygen concentration of the atmosphere leading up to the Great Oxidation Event at ∼2.4 Ga.